KESIAGAAN MASA DARURAT COVID-19 MELALUI SKRENING MANDIRI COVID-19 TERHADAP STIGMA PENDERITA - Noor Fitriyani; Intan Maharani Sulistyawati Batubara; Nurul Devi Ardiani (Journal of Nursing Care and Biomolecular, 2022)
Introduction: The Covid-19 has infected all countries in the world, including Indonesia. This condition affects the emergence of stigma to everyone because Covid-19 is a disease with rapid transmission. The stigma drives individuals to obscure unhealthy conditions and be reluctant to perform immediate health care. Therefore, it is essential to conduct COVID-19 self-screening actions. This study intended to determine the relationship between COVID-19 self-screening and the patients’stigma during the COVID-19 emergency. Methods: The research adopted a non-experimental descriptive with a correlational analytic method in which the researcher analyzes the COVID-19 self-screening with the patients' stigma. The instrument used a COVID-19 self-screening questionnaire and the stigma of COVID-19 patients. The sample was selected by total sampling with 45 respondents according to the inclusion and exclusion criteria. Result and analysis:  The statistical test result of the Spearman Rho correlation test obtained a p-value = 0.000 (p-value <0.05). In conclusion, the result revealed a relationship between COVID-19 self-screening and the patients’ stigma during the Covid-19 emergency.   Key words: stigma, screening, covid-19